Antecedents for success of e-commerce platforms: an investigative approach. (2017) - Ali, Asif; Rasool, Gowhar; Pathania, Anjali
A plethora of literature is available highlighting the critical success factors (CSFs) of information systems (IS). While most of the studies were elusive in determining CSFs, the research of DeLone and McLean (1992) proposed an IS success model which is most comprehensive and widely applied model in various research studies carried out in this context. The model was later updated to incorporate parsimony by DeLone and McLean (2003). The updated model is based on six success factors, i.e., system quality, information, service quality use, user satisfaction and net benefits. This paper attempts to examine the role of each critical success factors as suggested by DeLone and McLean (2003) towards the success of e-commerce platforms and how it can be leveraged for enhancing customer value by laying strong foundation on most vital factor. DeLone and McLean (2003) model was applied to make a comparison between Flipkart and Snapdeal which are two dominant players of e-commerce in India, so as to investigate the antecedents for the success of e-commerce platforms.